Acute allergic interstitial pneumonitis induced by hydrochlorothiazide. - Biron, P (1991)
OBJECTIVE: To examine the clinical features of 4 unpublished cases and 26 published cases of acute allergic interstitial pneumonitis induced by hydrochlorothiazide (HCT). DATA SOURCES: The unpublished cases were found in the database of the Drug Adverse Reaction Program, Health Protection Branch, Department of National Health and Welfare, and the database of the Programme conjoint de pharmacovigilance, in Quebec. The published cases were retrieved from MEDLINE and EMBASE. STUDY SELECTION: Reported cases were selected if they were sufficiently documented. All published cases were selected because a differential diagnosis had been made in each one. DATA SYNTHESIS: The onset was acute and dramatic; the average time to onset of symptoms was 44 minutes. Sex was a predominant risk factor, since 27 (90%) of the 30 patients were women. The average age was 56 years; thus, most of the women were postmenopausal. Over two-thirds of the patients had one to three positive prechallenges or rechallenges, 3 of the 52 documented adverse events occurred after a voluntary rechallenge, some were life-threatening and necessitated mechanical ventilation, and 1 was fatal. Treatment was supportive; avoidance of HCT was the only prevention. CONCLUSION: Acute allergic interstitial pneumonitis due to HCT is extremely rare and potentially fatal. Such a reaction can be diagnosed only if the clinician suspects it when presented with a case of unexplained acute pulmonary edema.